2008
DOI: 10.1063/1.2953082
|View full text |Cite
|
Sign up to set email alerts
|

Role of the buffer layer thickness on the formation of basal plane stacking faults in a-plane GaN epitaxy on r-sapphire

Abstract: Optical properties of nearly stacking-fault-free m -plane GaN homoepitaxial films grown by metal organic vapor phase epitaxy on low defect density freestanding GaN substrates

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…1(c) and (d). It is known that irregular size and anisotropic shape of nucleus results in a high density of partial dislocations, which is originated from the in-plane anisotropic strains of c-and m-directions [18]. Therefore AFM images of NLs indicated that a stable nucleation can be initiated at the thickness of 120 nm.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…1(c) and (d). It is known that irregular size and anisotropic shape of nucleus results in a high density of partial dislocations, which is originated from the in-plane anisotropic strains of c-and m-directions [18]. Therefore AFM images of NLs indicated that a stable nucleation can be initiated at the thickness of 120 nm.…”
Section: Resultsmentioning
confidence: 98%
“…To optimize the growth conditions and analyze growth behaviors of a-plane GaN on sapphire substrates, the surface and structural properties of a-plane GaN films were characterized by using atomic force microscopy (AFM), high resolution X-ray diffraction (HR-XRD), and transmission electron microscopy (TEM). (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) a-plane GaN films were grown on (1-102) r-plane sapphire substrates by using an AXITRON 11 Â 2 in. metal-organic chemical vapor deposition system based on planetary reactor.…”
Section: Introductionmentioning
confidence: 99%
“…There is a good lattice match along [0001] GaN//[1-101] Al 2 O 3 , while lattice mismatch is 16% along the [1-100] GaN// [11-20] Al 2 O 3 crystal directions. Furthermore, the growth rate along the c-direction is much higher than that along the m-direction, so the pleat morphology comes forth and produces the anisotropy [7,8].…”
Section: Resultsmentioning
confidence: 98%
“…This is due to the elimination of the strong built-in electric fields which play a role in limiting the radiative recombination efficiency of c-plane structures. However, it is now well established that non-polar films grown on foreign substrates such as r-plane sapphire and γ-LiAlO 2 suffer from high densities of threading dislocations and basal-plane stacking faults (BSFs) [1]. BSFs are extended planar defects that lie in the c-plane and can be considered as narrow inclusions of cubic phase (ZB) material in a wurtzite (WZ) matrix.…”
mentioning
confidence: 99%